Development of a flexible instrumented lumbar spine finite element model and comparison with in-vitro experiments - Leszczynski, Aleksander; Meyer, Frank; Charles, Yann-Philippe; Deck, Caroline; Willinger, Rémy (Computer methods in biomechanics and biomedical engineering, 2022)
Surgical corrections of degenerative lumbar scoliosis and sagittal malalignment are associated with significant complications, such as rod fractures and pseudarthrosis, particularly in the lumbosacral junction. Finite element studies can provide relevant insights to improve performance of spinal implants. The aim of the present study was to present the development of non-instrumented and instrumented Finite Element Models (FEMs) of the lumbopelvic spine and to compare numerical results with experimental data available in the literature. The lumbo-pelvic spine FEM was based on a CT-scan from an asymptomatic volunteer representing the 50th percentile male. In a first step a calibration of mechanical properties was performed in order to obtain a quantitative agreement between numerical results and experimental data for defect stages of spinal segments. Then, FEM results were compared in terms of range of motion and strains in rods to in-vitro experimental data from the literature for flexible non-instrumented and instrumented lumbar spines. Numerical results from the calibration process were consistent with experimental data, especially in flexion. A positive agreement was obtained between FEM and experimental results for the lumbar and sacroiliac segments. Instrumented FEMs predicted the same trends as experimental in-vitro studies. The instrumentation configuration consisting of double rods and an interbody cage at L5-S1 maximally reduced range of motion and strains in main rods and thus had the lowest risk of pseudarthrosis and rod fracture. The developed FEMs were found to be consistent with published experimental results; therefore they can be used for further post-operative complication investigations.